The castle of Androusa: Characterization of mortars and application of the Geographical Information Systems (GIS) - Βρυώνης, Παναγιώτης (Πανεπιστήμιο Πελοποννήσου, 2018)
The purpose of this research is the study of the castle of Androusa through the use of new technologies and archaeometric analytical techniques. The research focuses mainly on the fortification of the castle, the mortars used for its construction and the relation of the castle with its landscape. The study is divided into two parts. The first is the theoretical part. It includes a bibliographic overview of the medieval Frankish castles with main focus on the history and fortification of the castle of Androusa. In this part, there is also information about the building mortar materials. The second is the practical part of the study. It presents the implementation of the new GIS information systems in the study of the castle of Androusa and its interaction with the landscape. A representation of the fortification of the castle and the geophysical relief of Androusa is made with the use of ArcMap10 program. This process led to some important remarks about the castle and some interesting assumptions. In the practical part, the sampling process, the analytical techniques and the methodology followed for the analysis of 11 mortar samples collected from the castle of Androusa is also being described, providing detailed information on their materials and their manufacturing technology. By examining the composition of the mortar samples, an attempt to associate and determine the different building phases observed in the castle is made. The techniques applied for the study of mortars are Optical Digital Microscopy LED, Electronic Scanning Microscopy (SEM) equipped with X-ray Microanalyzer (EDX), X-ray Fluorescence (XRF) and Granulometric Analysis. At the end of the study there is an overview and evaluation of all the results of the techniques applied. Finally, there is a discussion about the conclusions and some suggestions for future research.
Keywords: Κάστρο της Ανδρούσας (Ανδρούσα, Ελλάδα); Κονίαμα -- Ανάλυση; Κονίαμα -- Έλεγχος; Αρχαιολογία -- Γεωγραφικά συστήματα πληροφοριών; Αρχαιολογία -- Μεθοδολογία; Κάστρα -- Ελλάδα -- Ανδρούσα; Οχυρωματικά έργα -- Ελλάδα -- Ανδρούσα; Ανδρούσα (Ελλάδα) -- Αρχαιότητες; Κάστρο Ανδρούσας; Ανάλυση κονιάματος; Γεωγραφικά συστήματα πληροφοριών; Αρχαιολογία